2012
DOI: 10.1097/aln.0b013e31824a88f5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Criteria for Type and Screen Based on Procedure's Probability of Erythrocyte Transfusion

Abstract: Background: At many hospitals, the type and screen decision is guided by the hospital's maximum surgical blood order schedule, a document that includes for each scheduled (elective) surgical procedure a recommendation of whether a preoperative type and screen be performed. There is substantial heterogeneity in the scientific literature for how that decision should be made. Methods: Anesthesia information management system data were retrieved from the 160,207 scheduled noncardiac cases in adults of 1,253 proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Ghirardo et al replicated these results in 3,424 patient undergoing moderate risk general surgery procedures and again found little evidence to support mandatory preoperative T&S in light of 0.32% overall RBC transfusion rate. 16 Finally, Dexter et al confirmed the threshold of 5% predicted individual transfusion risk as appropriate to trigger preoperative T&S. 17 Beyond institutional requirements another reason that T&S are oftentimes ordered is that surgeons tend to over-utilize laboratory testing, possibly for medico-legal reasons or in the case of vascular surgeons, due to habituation to high risk procedures. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghirardo et al replicated these results in 3,424 patient undergoing moderate risk general surgery procedures and again found little evidence to support mandatory preoperative T&S in light of 0.32% overall RBC transfusion rate. 16 Finally, Dexter et al confirmed the threshold of 5% predicted individual transfusion risk as appropriate to trigger preoperative T&S. 17 Beyond institutional requirements another reason that T&S are oftentimes ordered is that surgeons tend to over-utilize laboratory testing, possibly for medico-legal reasons or in the case of vascular surgeons, due to habituation to high risk procedures. 18 …”
Section: Discussionmentioning
confidence: 99%
“…The proposed model showed that 93% of all preoperative T&S can be avoided using the individual predicted transfusion risk of 5% as a threshold (Figure 2). 17 This offers substantial cost saving potential while maintaining patient safety at current standards; a major benefit in the current healthcare climate of limited resources. Based on our institutional cost of $350 for a standard T&S, the potential savings could amount to more than $5.2M in the studied NSQIP population.…”
Section: Discussionmentioning
confidence: 99%
“…The T&S protocol has been widely adopted by blood banks in North America and Europe in the mid-1980s [1]. The T&S protocol has been proven to be safe, efficient, and beneficial to the transfusion practice of hospitals [2, 3]. “Type” stands for the ABO and Rh typing, specifically the phenotype, and “screen” refers to testing for atypical antibodies that might cause transfusion problems.…”
Section: Introductionmentioning
confidence: 99%
“…A review of blood ordering habits and blood utilization statistics in audit studies can help in improving these services and initiate measures to regulate blood ordering and utilization. However, a strong institutional commitment is required for implementation of new policies, albeit the advantages to this approach have been noted [3, 5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, many hospitals have adapted a type and screen policy to dispense blood±blood products. In a report published by Dexter et al in 2012, the authors validated an approach to define an appropriate MSBOS, by reviewing more 160,000 noncardiac surgical cases from more than 1,250 procedures (13). The outcomes have been cost effective with no compromise on patient safety.…”
Section: Discussionmentioning
confidence: 99%